2010
DOI: 10.1186/1471-2229-10-103
|View full text |Cite
|
Sign up to set email alerts
|

Resistance loci affecting distinct stages of fungal pathogenesis: use of introgression lines for QTL mapping and characterization in the maize - Setosphaeria turcicapathosystem

Abstract: BackgroundStudies on host-pathogen interactions in a range of pathosystems have revealed an array of mechanisms by which plants reduce the efficiency of pathogenesis. While R-gene mediated resistance confers highly effective defense responses against pathogen invasion, quantitative resistance is associated with intermediate levels of resistance that reduces disease progress. To test the hypothesis that specific loci affect distinct stages of fungal pathogenesis, a set of maize introgression lines was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
100
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 78 publications
2
100
0
1
Order By: Relevance
“…In a QTL study of the recombinant inbred line (RIL) population Ki14 3 B73 evaluated for three foliar fungal diseases, NLB, GLS, and SLB, a 33-Mb region spanning bins 1.05 and 1.06 was the only locus identified that conferred resistance to all three diseases (Zwonitzer et al 2010). A number of QTL studies for NLB resistance in maize have identified QTL at bin 1.06, ranging in physical size from 3 to 30 Mb (Freymark et al 1993;Welz et al 1999;Wisser et al 2006;Chung et al 2010bChung et al , 2011Van Esbroeck et al 2010;Poland et al 2011). Additionally, bin 1.06 harbors the dominant Stewart's wilt resistance gene Sw1 (Ming et al 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In a QTL study of the recombinant inbred line (RIL) population Ki14 3 B73 evaluated for three foliar fungal diseases, NLB, GLS, and SLB, a 33-Mb region spanning bins 1.05 and 1.06 was the only locus identified that conferred resistance to all three diseases (Zwonitzer et al 2010). A number of QTL studies for NLB resistance in maize have identified QTL at bin 1.06, ranging in physical size from 3 to 30 Mb (Freymark et al 1993;Welz et al 1999;Wisser et al 2006;Chung et al 2010bChung et al , 2011Van Esbroeck et al 2010;Poland et al 2011). Additionally, bin 1.06 harbors the dominant Stewart's wilt resistance gene Sw1 (Ming et al 1999).…”
mentioning
confidence: 99%
“…The importance of genes localized to maize bin 1.06 in resistance to both NLB and Stewart's wilt has been described in multiple mapping populations. Using a population of Tx303 3 B73 introgression lines (Szalma et al 2007), Chung et al (2010b showed that the NLB resistance QTL at 1.06 protects against fungal penetration.To explore the genomic complexity of this important region, we constructed high-resolution mapping populations at this locus and evaluated NLB and Stewart's wilt resistance, using a set of Tx303 3 B73 near-isogenic lines (NILs) (Szalma et al 2007;Chung et al 2010b). Fine mapping allowed us to dissect the linkage relationship between the major-effect Stewart's wilt QTL and the minor-effect NLB QTL and to identify candidate genes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used QTLs on these chromosomes, as well as a QTL on chromosome 3 (Ogliari et al, 2007) and a QTL on chromosome 8 (Chung et al, 2010a;2010b;Wang et al, 2012).…”
Section: Association Mapping For the Resistance To Northern Leaf Blightmentioning
confidence: 99%